Analisis Sistem Informasi Akuntansi dengan Fitur Stok Telur Menggunakan Metode Fifo di UD Abah Muhdor Kab. Malang - Abdillah, Muhammad Ibnu; Hasan, Khojanah; Zaenuddin, Zaenuddin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to find out how the Accounting Information System is at UD Abah Muhdor and to find out the Accounting Information System using the FIFO method in egg stock at UD Abah Muhdor. The main focus of this study is whether there is an application of the Accounting Information System at UD Abah Muhdor and how the Accounting Information System uses the FIFO method in egg stock at UD Abah Muhdor. The method used in this study is qualitative descriptive analysis with data collection techniques through documentation, interviews, and observations. The results of this study found a problem in the accounting system for eggs where the calculation of egg stock still uses a simple method so that damage to the eggs often occurs. This finding requires an effective method, namely using the FIFO method so that the calculation of egg stock runs effectively and avoids damage to the eggs. This research is expected to improve the accounting information system on this farm, especially in calculating its egg stock.